2015
DOI: 10.3109/2000656x.2015.1049952
|View full text |Cite
|
Sign up to set email alerts
|

Free intra-osseous muscle transfer for treatment of chronic osteomyelitis

Abstract: The present study demonstrated that free intramedullary muscle transfers are effective in providing a high rate of success in the treatment of chronic osteomyelitis. The secondary filling of the intramedullary cavity after extensive removal of all infected bony sequesters has proven to give a long-term arrest of chronic osteomyelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Of the 260 muscle flaps where total flap loss rates were discussed, 27 flaps or 10.4% experienced total flap loss. 9,[11][12][13][14][15]17,21,23,24,27,29 Two fasciocutaneous flap studies reported total flap loss totaling to 5.3% (n ¼ 1). 9,23 Both of the grouped fasciocutaneous and muscle flap studies reported total flap loss amounting to 6 of the 127 flaps, or 4.7%.…”
Section: Total Flap Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 260 muscle flaps where total flap loss rates were discussed, 27 flaps or 10.4% experienced total flap loss. 9,[11][12][13][14][15]17,21,23,24,27,29 Two fasciocutaneous flap studies reported total flap loss totaling to 5.3% (n ¼ 1). 9,23 Both of the grouped fasciocutaneous and muscle flap studies reported total flap loss amounting to 6 of the 127 flaps, or 4.7%.…”
Section: Total Flap Lossmentioning
confidence: 99%
“…About 7.8% of muscle flaps in these pooled studies experienced partial flap loss (n ¼ 16 of 205). 1,11,[13][14][15]23,24,26 Two fasciocutaneous flap studies reported partial flap loss totaling to 3.6% (n ¼ 1 of 28). 23,33 This was not a statistically significant difference in outcomes between the two groups (p ¼ 0.701).…”
Section: Partial Flap Lossmentioning
confidence: 99%
“…However, the radical debridement itself creates a dead space in the depth of the wound, which may cause spread of infection and resultant loss of larger tissues if not filled adequately. The muscular flap is considered a stronger anti‐infective, vascularized tissue than other flaps like the de‐epithelialized skin flap because it has robust blood supply 45,46–51 . With the aim of dissecting the DIEA towards the distal end and including as many muscular branches as possible, the rectus muscle mass in our chimeric DIEP flap served well as no infection was found in our case series.…”
Section: Discussionmentioning
confidence: 77%
“…Osteomyelitis is generally highly dependent on the degree of damage to the soft tissue envelope 1) ; therefore, replacement of the surrounding tissue may be required. Many previous reports have demonstrated the versatility of muscular or fascial flaps for osteomyelitis of the long bones or bones of the trunk [2][3][4][5] ; however, few have described such efforts in cases involving digital bones. According to previous reports, the cure rates of osteomyelitis are comparable between muscular and fascial flaps, and fascial or fasciocutaneous flaps have advantages in terms of aesthetic results and donor-site morbidity [6][7][8] .…”
Section: Discussionmentioning
confidence: 99%